The levels of resistin and other adipokines in patients with hypothyroidism - N I Verbovaia; I Iu Kapralova; A F Verbovoĭ (Терапевтический архив, 2014)
AIM. To investigate the relationship of resistin, adiponectin, leptin, and hormone metabolic parameters in patients with hypothyroidism. MATERIALS AND METHODS. Ninety-three women aged 58.0 (53.0-63.0) years with hypothyroidism were examined. A control group consisted of 10 women aged 48 (47-50) years. Anthropometric characteristics, glucose and lipid metabolic parameters, and leptin, resistin, adiponectin levels were studied. RESULTS. The patients with hypothyroidism were found to have statistically significantly enhanced insulin resistance (IR) and compensatory hyperinsulinemia in the presence of android fat distribution. The found atherogenic dyslipidemia manifested itself as an increase in the levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, and atherogenic index and as a reduction in high-density lipoprotein cholesterol. The concentration of leptin and resistin was increased and that of adiponectin was reduced in the patients with hypothyroidism. There was a correlation of leptin and adiponectin with fat metabolic parameters. CONCLUSION. The women with hypothyroidism had enhanced IR, as well as compensatory hyperinsulinemia in the presence of android fat distribution. Hypothyroidism is accompanied by the development of atherogenic dyslipidemia. The concentration of leptin and resistin was elevated and that of adiponectin was reduced in the examinees.